KEKERASAN TERHADAP PEREMPUAN DALAM NASKAH DRAMA MONOLOG MARSINAH MENGGUGAT KARYA RATNA SARUMPAET - Maharani, Atri Suci; WS, Hasanuddin; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2018)
This study aims to: (1) describe the form of violence against women; (2) to describe the causes of violence against women; and (3) to describe the impact of violence against women in the drama of Marsinah monologue by RatnaSarumpaet. This research type is qualitative research by using descriptive method. The data in this study are sentences and direct speeches of figures that can be interpreted or interpreted as violence against women. Sources of data in this research is the script of Marsinah monologue drama Menggugat works RatnaSarumpaet. The research stages are done by following steps: (1) reading drama script and (2) inventorying data. After data is collected, then analyzed by the following steps: (1) classifying data; (2) to interpret data; and (3) make a conclusion. Based on the result of the research, it can be concluded that the indicators of violence against women in Marsinah monologue drama Scriptures sued by RatnaSarumpaet include: (1) violence against women is divided into five, namely exploitation, powerlessness, marginalization, cultural imperialism, and violence. Violence is divided into two, namely physical violence, including persecution, rape and murder, and internal violence, including humiliation and threats. (2) the cause of violence against women is divided into two, namely internal and external factors; and (3) the impact of violence against women is divided into two, namely the impact of violence against the physical, including fractures, bruises, and severe injuries, and the impact of nonphysical violence, including fear, humiliation and low self-esteem.Â Keywords: violence, women, Marsinah Menggugat